Another Athanasius : four Sahidic homilies attributed to Athanasius of Alexandria : two homilies on Michael the Archangel, the Homily on Luke 11:5-9 and the Homily on Pentecost - Pseudo-Athanasius, (Corpus scriptorum Christianorum Orientalium. Scriptores Coptici ;, 2019)
"Many Coptic literary texts are circulated under the name of Athanasius of Alexandria, the Alexandrian Archbishop and Theologian (ca. 296/298-2 May 373). Although there are strong evidences that most of these texts are falsely attributed to him, they are of extreme importance for the study of Coptic Christianity. The four homilies, edited and translated in this two volumes book, present 'Another Athanasius' to those who knew the history of their pseudo-Author. The homilies present Athanasius as a close friend of Pachomius, the Archimandrite of Upper Egypt (ca. 292-348). A visit of Pachomius to Alexandria is described in details. One homily relates about Athanasius' escape to Upper Egypt. Another homily contains fanciful acts of the Nicene council. The last homily presents Athanasius as a preacher while giving a long talk on the Christian household. This corpus of texts reveals the mental image of Athanasius in the Coptic mentality through centuries after his death."--